The Transformation of Risk Management in Islamic Financial Institutions: A Sharia Economic Law Perspective - Harjoni Desky; Zulhamdi Zulhamdi; Asmah Savitri (Department of Islamic Economic Law, Faculty of Sharia, Sultanah Nahrasiyah State Islamic University, Lhokseumawe, 2025)
Risk management in Islamic financial institutions presents a unique challenge due to the dual necessity of aligning with conventional management practices and the legal-ethical framework of Sharia. The central problem of this research is the lack of integration between evolving risk management practices and the foundational principles of Sharia Economic Law, which often leads to either operational inefficiency or potential non-compliance with Islamic legal norms. This disconnect becomes more critical due to increasing financial complexity, technological innovation, and regulatory demands. Therefore, this study addresses the following research question: How is risk management transforming within Islamic financial institutions, and to what extent does this transformation comply with the principles of Sharia Economic Law? The study also explores whether such transformation strengthens the Islamic finance sector's legal certainty, stakeholder trust, and institutional resilience. This research adopts a qualitative-descriptive method with a normative legal approach. Data were collected through document analysis of legal provisions, fatwas, and risk management frameworks used in selected Islamic financial institutions. In-depth interviews with Sharia board members and risk officers from Islamic banks were also conducted to capture practical insights and legal reasoning. The findings show that the transformation of risk management in Islamic financial institutions is occurring on three fronts: technological adoption (e.g., AI and big data for risk analysis), regulatory compliance alignment (integration of OJK and DSN-MUI standards), and internal policy development grounded in maqashid al-shariah. However, the study finds inconsistencies between implementation and Sharia legal standards, particularly in credit and liquidity risks, where conventional models are still dominant. The research concludes that a robust Sharia Economic Law framework and ethical managerial reform is essential to ensuring that risk management practices in Islamic financial institutions mitigate risk and uphold Islamic legal and moral obligations